APPLICATION OF MULTI-SERVER QUEUING MODEL TO ANALYZETHE QUEUING SYSTEM OF OPD DURING COVOD-19 PANDEMIC: A CASE STUDY - Khaskheli, Sarmad Ali; Kalwar, Hamid Ali; Kalwar, Muhammad Ahmed; Marri, Hussain Bux; Khan, Muhammad Ali; Nebhwani, Murlidhar (The journal of contemporary issues in business and government, 2021)
The purpose of this research paper was to suggest the optimum service level of queuing system of reception and the outpatient department during COVID-19 pandemic. The data was collected from the reception and OPD of the ABC public hospital of Hyderabad. Data included, the arrival times, service times of patients and number of doctors and receptionist at the workplace, their salaries and waiting cost of patients. Input analysis of patients` arrivals and service was conducted by in input analyzer of Rockwell Arena software. TORA optimization software was used for the calculation of performance measures. Various costs of queuing system were calculated in MS Excel and the required graphs were also plotted. After the in-depth analysis, it was revealed that one receptionist and one doctor should be increased to bring optimality in the queuing system and patients` flow. After this decision, waiting cost of patients decreased to greater extent.